Impact of Customer’s Perception on Green Banking Development: A Study in the Kathmandu Valley - Yadav, Shristy; Gahatraj, Ichchha; Nishant, Arya; Shrestha, Mohit Bahadur (New Perspective: Journal of Business and Economics, 2025)
The concept of green banking emphasizes environmentally sustainable practices in banking, focusing on reducing carbon footprints and paper usage. This study aims to explore how various factors—awareness level, willingness to adopt green banking, determinants, benefits, and challenges of green banking—affect customer perception of green banking practices. A quantitative survey was conducted involving 120 bank customers from Kathmandu Valley to examine these relationships. The statistical analysis showed that customer perception of green banking is significantly influenced by the determinants and challenges associated with green banking. In contrast, awareness level, willingness to adopt green banking, and the perceived benefits of green banking did not have a significant impact on customer perception. These findings highlight the importance of addressing specific determinants and challenges to improve customer acceptance and support for green banking initiatives.